Teaching Phonetics Using A Mobile-Based Application in an EFL Context - Haggag, Haggag Mohamed (European Scientific Journal, ESJ, 2018)
Mobile based learning has been an effective mean for learning languages. The aim of this study is three-fold: first, to investigate the process of designing mobile-based application for teaching phonetics in EFL context. The second is to verify the effect of this mobile application on pre-service EFL teachers' achievement of English phonetics at a university level. Finally, it aims to investigate participants' satisfaction towards Mobile Assisted Language Learning. The research implements a mobile based program for developing preservice teachers' segmental elements in a phonetics courses. It deals with how to design the program, implement it and test its results. Participants of the study were (23) pre-service English language teachers at Hurghada Faculty of Education, South Valley University, Egypt. Instruments of the study included a mobile based phonetics module, English phonetics achievement Test and an English Satisfaction scale. Results showed a development in participants' achievement at the level (0.01) in mastering the segmental elements (Phonemes identifications- consonants classificationvowels classification). Participants showed their satisfaction of the application through their positive feedback and responses to the items of the questionnaire